Ireland's Tax Expenditure System: International Comparisons and a Reform Agenda - Studies in Public Policy No. 24 - COLLINS, MICHEAL (Policy Institute, Trinity College Dublin, 2010)
Tax Expenditures, also known as tax incentives or tax breaks, represent an infrequently explored and little understood area of Irish public policy. Despite this, they account for more than ?11 billion per annum in exchequer revenue forgone ? equivalent to over 5.5% of GDP and more than one-fifth of total tax revenue (2006 figures). This paper examines the current tax expenditure regime in Ireland and highlights the role that tax expenditures should play in the Budgetary adjustment planned for late 2010 and in subsequent years. The paper first reviews the nature and scale of Ireland?s tax expenditure system in a national and international context. It then considers their impact, advantages, limitations and consequences. Finally the paper outlines a series of reforms to tax expenditures; reforms which if implemented would yield the exchequer considerable savings and establish a more appropriate and better administered tax expenditure system.
PUBLISHED
Keywords: Taxation; Tax Expenditure; Economics; Taxation; Tax Expenditure